2005
DOI: 10.1021/bi051305z
|View full text |Cite
|
Sign up to set email alerts
|

The Heme of Cystathionine β-synthase Likely Undergoes a Thermally Induced Redox-Mediated Ligand Switch

Abstract: Cystathionine beta-synthase (CBS) is a pyridoxal-5'-dependent enzyme that catalyzes the condensation of homocysteine and serine to form cystathionine. Human CBS is unique in that heme is also required for maximal activity, although the function of heme in this enzyme is presently unclear. The study presented herein reveals that the heme of human CBS undergoes a coordination change upon reduction at elevated temperatures. We have termed this new species "CBS424" and demonstrate that its formation is likely irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 55 publications
6
78
0
Order By: Relevance
“…Our previous results indicated that heme does not function in redox sensing, ligand binding, or catalysis but rather supported the structural role of heme in proper folding and/or subunit assembly (22,28,(32)(33)(34)(35). With respect to this hypothesis and the presented data, heme saturation could serve as a marker for properly folded CBS and could be indicative of the activity of purified CBS.…”
Section: Discussionsupporting
confidence: 57%
“…Our previous results indicated that heme does not function in redox sensing, ligand binding, or catalysis but rather supported the structural role of heme in proper folding and/or subunit assembly (22,28,(32)(33)(34)(35). With respect to this hypothesis and the presented data, heme saturation could serve as a marker for properly folded CBS and could be indicative of the activity of purified CBS.…”
Section: Discussionsupporting
confidence: 57%
“…As we mentioned before in this studies, we named the new species as the P420 form if its ferrous CO-binding absorbance spectrum showed a Soret maximum around 420 nm. After heating at 48 for more than 30 min, intensity of ℃ the Soret band decreased obviously. But the existence of a 416 nm Soret band in absorbance spectrum and a 419 nm in CD spectrum (as described later, Figure 3C) indicated the heme of P450 2C8 was still buried in the heme pocket at 48 .…”
Section: Thermal Unfolding Of P450 2c8mentioning
confidence: 98%
“…But the existence of a 416 nm Soret band in absorbance spectrum and a 419 nm in CD spectrum (as described later, Figure 3C) indicated the heme of P450 2C8 was still buried in the heme pocket at 48 . When the temperature was cooled ℃ from 48 to 20 ℃ , the intensity of the Soret band i ℃ ncreased apparently without wavelength shift ( Figure 3A inset).…”
Section: Thermal Unfolding Of P450 2c8mentioning
confidence: 99%
“…In contrast to CO, NO ⅐ binding to Fe(II)-CBS results in a pentacoordinate iron-nitrosyl Fe(II)NO ⅐ -CBS species with a Soret maximum at 394 nm, indicating the loss of both endogenous axial ligands (34 (32). In addition, Fe(II)-CBS can slowly decay to an inactive Fe(II)424-CBS form with a Soret maximum at 424 nm, in which the cysteine is replaced by an unidentified neutral ligand (35,36). Although Fe(II)424-CBS formation is promoted under nonphysiological conditions such as high temperature (36), the biological significance of this process is not clear.…”
mentioning
confidence: 99%
“…In addition, Fe(II)-CBS can slowly decay to an inactive Fe(II)424-CBS form with a Soret maximum at 424 nm, in which the cysteine is replaced by an unidentified neutral ligand (35,36). Although Fe(II)424-CBS formation is promoted under nonphysiological conditions such as high temperature (36), the biological significance of this process is not clear. We have demonstrated recently that Fe(II)-CBS has the ability to reduce nitrite (NO 2 Ϫ ) to NO ⅐ , leading to Fe(II)NO ⅐ -CBS formation, suggesting a possible new role for CBS in NO ⅐ signaling (37).…”
mentioning
confidence: 99%